(untitled) (Al-Qamar, 2020)
This article presents a comparative analysis of the biomedical and Islamic view points on the concepts of marriage as an institution of reproduction, infertility and the need and necessity to carry out and put into service contemporary Assisted Reproductive Techniques (ARTs) when the spouses are affected with the full or partial infertility. There is a common connotation that the Sharī‘ah rejects all forms of ARTs but this research nullifies this assumption and gives rational reasons when a technique is rejected and provides reasons too when any such technique is accepted under Islamic law. ARTs like Artificial Insemination, In-Vitro Fertilization (IVF), Donor Eggs and Donor Sperms, Surrogacy and Cloning have been discussed in the light of Sharī‘ah rulings in order to examine the conditions for their permissibility by evaluating their nature and medical process.